“It is not easy”: Experiences of people living with HIV and tuberculosis on Tuberculosis treatment in Uganda - Ruth Nabisere-Arinaitwe; Lydia Namatende-Sakwa; Josephine Bayiga; Juliet Nampala; Lucy Alinaitwe; Florence Aber; Brian Otaalo; Joseph Musaazi; Rachel King; Mike Kesby; Derek J. Sloan; Christine Sekaggya-Wiltshire (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2023)
Background: Completion of tuberculosis (TB) treatment presents several challenges to patients, including long treatment duration, medication adverse-effects and heavy pill burden. WHO emphasize the need for patient-centered TB care, but such approaches require understanding of patient experiences and perceptions. Methods: In 2020, we nested a qualitative study within a clinical trial that recruited 128 HIV-TB co-infected adults in Kampala receiving rifampicin-based TB treatment, alongside anti-retroviral therapy. A purposively selected sub-sample of 46 trial participants contributed to nine gender segregated focus group discussions. Of these, 12 also participated in in-depth interviews. Sessions were recorded, transcribed verbatim and translated from local languages into English. Thematic analysis focused on drug adverse-effects, use of self-prescribed medications and barriers to treatment adherence. Results: Patients seemed more concerned about adverse effects that clinicians sometimes overlook such as change in urine color. Those who remembered pre-treatment counselling advice were disinclined to manage adverse-effects by self-prescription. Difficulty in accessing a medical practitioner was reported as a reason for self-medication. Obstacles to adherence included stigma (especially from visible adverse-effects like “red urine”), difficulties with pill size and number, discomfort with formulation and medication adverse effects. Conclusion: Tailored pre-treatment counselling, improved access to clinical services, and simpler drug administration will deliver more patient-centered care.